Micromorphological studies of leaf epidermal features in populations of maples (Acer L.) from Iran - Mohtashamian, Mojgansadat; Attar, Farideh; Kavousi, Kaveh; Masoudi-Nejad, Ali (Phytotaxa, 2017)
As the largest genus of broad leaved deciduous trees, Acer L. contains about 126 species distributed in the temperate regions of the Northern Hemisphere. With eight native species in Iran, maples are among the most important tree species in the country. Micromorphological traits of 39 populations of Iranian native species indicated the value of leaf epidermal characteristics in identification and classification of maples. A number of epidermal morphological features of the abaxial surface were investigated using LM and SEM images. The occurrence of stomata in clusters is reported for the first time in Acer. The shape of the epidermal cells, anticlinal cell wall patterns, type of indumentum, and epicuticular waxes were the most significant variables in this study. The ability of quantitative and qualitative variables in segregating the studied taxa was evaluated by statistical methods, including PCA, MCA and Non-parametric analyses.